The Design of Accident Detection and Tracking Systems on Motorcycles - Febi Ramadaniati (Teknik Elektro Politeknik Negeri Padang, 2021)
Motorcycles are type of vehicles with the highest accidents percentage every year. The location away from the settlement and the time of the accident is one of the factors that slow down the spread of information about accidents. This study aims to make a tool that can send such information in the form of notifications and crash site points to the victims’ families. Testing was conducted by looking at the sensor response detecting tilt on the motorcycle against the large reading angle. Furthermore, GPS module accuracy testing is conducted in reading the location by comparing GPS module readings with actual location points in Google apps Maps which is then calculated by using the Haversine Formula method up to gsm module capability testing for send SMS notifications in the form of latitude, longitude, and links that can connect to the Google Maps app. Based on the results of the trials and analyses that have been conducted, the slope sensor response area to transmit crash notification is <=50° or >=50°. After that, the GSM module will send notifications and location points detected by the GPS module with an average reading difference of 2.97 meters.